Comparison of Self-Differentiation and Interpersonal Forgiveness between Veterans\'- and Non-Veterans\' Spouses - S. Bashardoust; P. Bagheri Matin (Afarand Scholarly Publishing Institute, 2020)
Abstract Aims: This study aimed to identify the differences between interpersonal forgiveness and self-differentiation in veteranschr('39')- and non-veteranschr('39') spouses. Instrument & Methods: The present study is non-experimental and conducted by the causal-comparative method in all the spouses of 25% of the veterans referred to the Damavand Martyrs and Veterans Affairs Foundation, the spouses of non-veterans living in Damavand in 2020. A total of 80 people (40 veteranschr('39') spouses and 40 non-veteranschr('39') spouses) were randomly selected. The research instruments included the self-differentiation scale and interpersonal forgiveness scale. Multivariate analysis of variance in SPSS 20 software was used to analyze the data. Findings: There was a significant difference between the two groups of veterans chr('39')and non-veteranschr('39') spouses in the component of my status from their differentiation variable (p<0.05), but no significant difference was observed for the components of emotional responsiveness, emotional fault, and integration with others (p>0.05). Also, there was no significant difference in reconnection and revenge control components, control of suffering, and realistic understanding of the interpersonal forgiveness variable (p>0.05). Conclusion: Veteranschr('39') spouses are more capable than non-veterans spouses of maintaining their individuality and independence in intimate relationships with others, as well as the balance between reason and emotion.